Spectral properties and observables in ultracold Fermi gases - Dizer, Eugen; Horak, Jan; Pawlowski, Jan M. (Physical review, 2024)
We calculate nonperturbative self-consistent fermionic and bosonic spectral functions of ultracold Fermi gases with the spectral functional approach. This approach allows for a direct real-time computation of nonperturbative correlation functions, and in the present work we use spectral Dyson-Schwinger equations. We focus on the normal phase of the spin-balanced Fermi gas and provide numerical results for the full fermionic and bosonic spectral functions. The spectral functions are then used for the determination of the equation of state, the Tan contact, and ejection rf spectra at unitarity. These results are compared to experimental data, the self-consistent 𝑇-matrix approach, and lattice results. Our approach offers a wide range of applications, including the ab initio calculation of transport and spectral properties of the superfluid phase in the BCS-BEC crossover.
Online veröffentlicht: 5. Juni 2024
Gesehen am 05.09.2025